Evaluating The Effectiveness of Digital Bibliotherapy in Enhancing Language Intellectual Development in Children with Speech Delay - Salsabilla, Aulia Aziz; Likawati, Anggun Kurnia; Mufidah, Afifah Dwi (Faculty of Language and Literature Education, Universitas Pendidikan Indonesia, 2023)
An important aspect of children's development is how they learn to speak and use language. Language and speech will be their main tools to communicate and socialize with others. However, some children experience difficulties in developing language and speech that prevent them from expressing themselves. This challenge is commonly referred to as speech delay. In response to the critical need to address speech delay in children, we have developed an innovative initiative called Bestari App. It is a digital bibliotherapy application designed to provide customized support to children with language learning challenges, particularly those with speech delays. The app is still in the development stage. Therefore, our study aims to investigate the effectiveness of the Bestari App in improving the language skills of children with speech delays. In this research, we conducted an experimental study using the case study method with the object of 2 (two) 10-year-old students who indicated speech delay. The experiment involved a series of six sessions using intervention techniques and instructional methods facilitated through the use of the Bestari application. Based on the following method, the results of the study were an increase in the post-test score of AD by 77% with an initial score of 35 to 62 and AT by 33% with an initial score of 62 to 82. From these results, it can be concluded that the Bestari App is effective enough to improve language skills in children with speech delay. However, the application still needs further development to maximize the existing results.